2023
DOI: 10.3233/jhd-220552
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis of Plasma in Huntington’s Disease Transgenic Sheep (Ovis aries) Reveals Progressive Circadian Rhythm Dysregulation

Abstract: Background: Metabolic abnormalities have long been predicted in Huntington’s disease (HD) but remain poorly characterized. Chronobiological dysregulation has been described in HD and may include abnormalities in circadian-driven metabolism. Objective: Here we investigated metabolite profiles in the transgenic sheep model of HD (OVT73) at presymptomatic ages. Our goal was to understand changes to the metabolome as well as potential metabolite rhythm changes associated with HD. Methods: We used targeted liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Notably, samples from 7-year-old HD sheep exhibited an increased number of altered metabolites and a greater shift in the acrophase compared to control sheep. Furthermore, the dysregulated metabolites identified in HD sheep showed remarkable similarity to those found in human patients, particularly involving phosphatidylcholines, amino acids, urea, and threonine ( Morton, 2023 ; Spick et al, 2023 ).…”
Section: Animal Models For Hd Researchmentioning
confidence: 81%
See 1 more Smart Citation
“…Notably, samples from 7-year-old HD sheep exhibited an increased number of altered metabolites and a greater shift in the acrophase compared to control sheep. Furthermore, the dysregulated metabolites identified in HD sheep showed remarkable similarity to those found in human patients, particularly involving phosphatidylcholines, amino acids, urea, and threonine ( Morton, 2023 ; Spick et al, 2023 ).…”
Section: Animal Models For Hd Researchmentioning
confidence: 81%
“…These results reaffirm the suitability of HD sheep as a valuable large animal model for preclinical assessment of HD therapies and, importantly, for noninvasive evaluation of therapeutic efficacy ( Taghian et al, 2022 ). In a recent metabolomics study, Spick et al ( 2023 ) observed significant absolute and rhythmic differences in metabolites between HD sheep at 5 and 7 years of age compared to age-matched control sheep. Notably, samples from 7-year-old HD sheep exhibited an increased number of altered metabolites and a greater shift in the acrophase compared to control sheep.…”
Section: Animal Models For Hd Researchmentioning
confidence: 98%
“…These sheep have 73 full-length repeated CAG amplification units of human cDNA transgenes. However, they lack both clear behavioral changes and structural changes in the brain [54], with only subtle neuropathology [55] and few postmortem (PM) changes in the cerebellar and liver metabolism [56], indicating that the sheep, even at 5 years of age, are still in the pre-symptomatic stage of HD. An advantage of the HD sheep model is that it can be monitored long-term to document metabolic alterations in the course of development, which enables the progression of the disease to be monitored through metabolic alterations such as rate markers or disease progression [57].…”
Section: Animal Studiesmentioning
confidence: 99%
“…In another previously conducted study investigating metabolite profiles using LC/MS in a transgenic sheep model of HD (OVT73) at pre-symptomatic ages, the circadian rhythmicity of metabolites (notably, phosphatidylcholines, amino acids, urea, and threonine) was found to be dysregulated in pre-symptomatic sheep. Alterations in the metabolomic profile could be used to differentiate the HD sheep from controls at 5 years of age [54].…”
Section: Animal Studiesmentioning
confidence: 99%
“…OVT73 are a premanifest model expressing an 11,625 bp transgene consisting of full length human HTT cDNA with an exon 1 repeat (CAG)69(CAACAG)2, under the control of a minimal human HTT promoter (1.1 Kb genomic DNA immediately upstream of exon 1) [28]. The OVT73 model develops HTT positive aggregates, gene expression and metabolic changes in the brain but no discernible cell loss [28][29][30][31][32][33][34][35][36][37][38][39][40]. The transgene is integrated as multiple copies at a single locus in an intergenic region of ovine chromosome 10, with approximately 10 full length copies integrated head-to-tail, surrounded by several smaller transgene fragments that lack promoter sequence [30].…”
mentioning
confidence: 99%